2023
DOI: 10.3390/ijms24054776
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Markers of Clinical Outcomes in Severe Mental Illness: A Systematic Review

Abstract: The term severe mental illness (SMI) encompasses those psychiatric disorders exerting the highest clinical burden and socio-economic impact on the affected individuals and their communities. Pharmacogenomic (PGx) approaches hold great promise in personalizing treatment selection and clinical outcomes, possibly reducing the burden of SMI. Here, we sought to review the literature in the field, focusing on PGx testing and particularly on pharmacokinetic markers. We performed a systematic review on PUBMED/Medline,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…Studies investigating the role of CYP in patients on clozapine have found opposite results indicating no association between CYP functional activity and change in PANSS overall symptom severity scores [ 30 , 41 ]. Furthermore, a recent systematic review demonstrated mixed findings regarding CYP2D6’s role, with most studies reporting no significant association with PANSS overall scores and few reporting slight associations with subscales of positive domains [ 42 ]. This suggests that CYP2D6, among others, may play a role in medications that target positive and cognitive symptom domains, however, more research is needed to uncover its true association.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating the role of CYP in patients on clozapine have found opposite results indicating no association between CYP functional activity and change in PANSS overall symptom severity scores [ 30 , 41 ]. Furthermore, a recent systematic review demonstrated mixed findings regarding CYP2D6’s role, with most studies reporting no significant association with PANSS overall scores and few reporting slight associations with subscales of positive domains [ 42 ]. This suggests that CYP2D6, among others, may play a role in medications that target positive and cognitive symptom domains, however, more research is needed to uncover its true association.…”
Section: Discussionmentioning
confidence: 99%